N-Rich Carbon Catalysts with Economic Feasibility for the Selective Oxidation of Hydrogen Sulfide to Sulfur - Yang, Can; Ye, Hanfeng; Byun, Jeehye; Hou, Yidong; Wang, Xinchen (American Chemical Society, 2020)
Y The efficient removal of hydrogen sulfide (H2S) from exhaust emissions is a great challenge to chemical industries. Selective catalytic oxidation of H2S into elemental sulfur is regarded as one of the most promising approaches to alleviate environmental pollution, while recycling sulfur resources. It is therefore highly desirable to develop efficient catalysts for the conversion of H2S to sulfur under mild reaction conditions. Here we present a nitrogen-rich carbon obtained by the direct thermal treatment of commercial polyaniline (PANI) for the selective oxidation of H2S in a continuous way at relatively low temperature (180 degrees C). The efficient conversion of H2S over the N-rich carbon catalysts was attributed to the in situ generation of pyridine-N on the carbon matrix, which served as the active sites to promote the absorption and dissociation of H2S molecules, achieving a superior catalytic conversion rate of 99% and selectivity up to 95% at 180 degrees C.